Managing sustainable consumption of durable goods - A systematic literature review = Zarządzanie zrównoważoną konsumpcją dóbr trwałego użytku - systematyczny przegląd literatury - Piwońska, Kalina; Urbańska, Michalina; Pilarska, Eliza; Miniszewski, Maciej; Staniszewski, Jakub; Kryszak, Łukasz (Zielona Góra: Faculty of Economics and Management Press)
The production and use of durable goods have severe consequences for the natural environment. Reducing those influences is highly desirable and is possible to achieve by changing customers` preferences and promoting the purchase and usage of more green or eco-friendly substitutes.
Keywords: durable goods; sustainable development; natural environment; willingness to pay; price premium; dobra trwałego użytku; rozwój zrównoważony; środowisko naturalne; gotowość do zapłaty; premia cenowa